COORDINATIVE ABILITY VARIABLES AMONG TENNIS AND SQUASH MEN PLAYERS – A COMPARATIVE STUDY. Issue 7 (11th March 2014) - Syed, I; Kanniyan, A; Al Moslim, H; Syed, MA
Abstract : Background: Sports performance is achieved through working, training of all major components i.e. technique coordination, tactics, physical fitness and psychological qualities. This apart coordinative abilities like orientation, differentiation, reaction, balance and rhythm play a big role. Objective: The objective of the study was to determine the relationship among coordinative abilities between Tennis and Squash men players. Design: Cross-sectional. Participants: The samples were 20 Tennis and 30 Squash Inter University players between 18–25 years. Main outcome measurements: The coordinative abilities studied were orientation, differentiation, reaction, balance and rhythmic. Test items used for different abilities were Zigzag run, backward medicine ball throw, lateral jumping ability, beam walk and long nose tests to find the difference in performance of the players. Mean, standard deviation and 't' test were used as statistical tools and level of significance was 0.05 . Results: The study showed quite interesting results as the game of tennis and squash are racket games and have many skills very similar to each other. The difference lies in the area of the court, the equipment used for play and the time limit of game. Tennis players have shown better performance in Orientation, differentiation, balance and rhythmic abilities due to the above difference and is in line with other studies done by Lees (2008), Miller, et al. (2001) etc. The only variable in which the squash players have shown some significance is the reaction ability which may be due to small area of play and the need to be quick as the time is too short to respond to the shots during the game. Conclusion: It is concluded that there exists significant difference in terms of all the coordinating abilities between the tennis and squash players and that the tennis players possessed better coordinating abilities than the squash players.